The Impact of Social Forestry on Communities and Forest Areas Salimbutan Lubuk Alung - Rinaldi Rinaldi; Eri Barlian; Nurhasan Syah; Iswandi Umar (Postgraduate, University of Mataram, 2024)
Indonesia is one of the countries that has the largest area of ​​natural forest in the world and is often referred to as one of the world's lungs which contributes oxygen for the survival of living things. Even though forests have many benefits, if the benefits from forests are not managed properly and correctly, they can have negative impacts and can lead to disasters and conflicts, apart from that, there is a fairly high level of deforestation and poverty is still often found in communities in and around forests. made various parties including the Ministry of Environment and Forestry try to encourage community empowerment programs. One of these community empowerment programs is Social Forestry. This type of research uses a quantitative approach with a descriptive design in the form of a case study. The population used in this research is the area and managers of LPHN Salimbutan Lubuk Alung, Padang Pariaman Regency. The samples from this research are all areas managed by LPHN Lintasutan Lubuk Alung. The instruments used in this research were observations and questionnaires. The results of this research show that in 2017 the level of deforestation at the Salimbutan LPHN increased by 9.7 Ha, then in 2018 it decreased by 2.6 Ha, in 2019 by 0.8 Ha, in 2020 by 1.4 Ha, in 2021 with a total of 0.8 Ha, and then in 2022 it will increase again with a total of 4.7 Ha. Meanwhile, community income before the training and assistance was still relatively low with a percentage of 11.16%. The data after training and assistance was carried out in the Salimbutan LPHN area, community income increased by 28.08% in 2022 and 57.38% in 2023